2005
DOI: 10.1213/01.ane.0000175209.61051.7f
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin in Hemorrhagic Shock

Abstract: We describe the treatment of two patients with hemorrhagic shock unresponsive to volume replacement and catecholamines. Both patients responded to a small-dose infusion of vasopressin, which allowed tapering off of the catecholamines. The possible role of small-dose infusions of vasopressin in fluid- and catecholamine-resistant hemorrhagic shock is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 4 publications
1
24
0
5
Order By: Relevance
“…Rationale: The use of any vasopressor in the treatment of hemorrhagic shock in humans has been evaluated thus far in scattered case reports, four medical record reviews, one prospective cohort study, and one RCT. [24][25][26][27][28][29][30][31] Two negative studies 25,31 have shown an association with increased mortality in patients who received vasopressors, but the remaining studies show positive outcomes with respect to survival. Most studies involved the use of vasopressin 24,25,27,29,30 (see next section).…”
Section: Statement: Epinephrine Increases Metabolic Abnormalities Commentioning
confidence: 99%
See 1 more Smart Citation
“…Rationale: The use of any vasopressor in the treatment of hemorrhagic shock in humans has been evaluated thus far in scattered case reports, four medical record reviews, one prospective cohort study, and one RCT. [24][25][26][27][28][29][30][31] Two negative studies 25,31 have shown an association with increased mortality in patients who received vasopressors, but the remaining studies show positive outcomes with respect to survival. Most studies involved the use of vasopressin 24,25,27,29,30 (see next section).…”
Section: Statement: Epinephrine Increases Metabolic Abnormalities Commentioning
confidence: 99%
“…Rationale: Promising studies of hemorrhagic shock in animal models have shown vasopressin improves organ perfusion and survival. In humans, there are three cases 27,29 of vasopressin use leading to return of spontaneous circulation or resolution of shock in patients with hemorrhagic shock unresponsive to fluids or catecholamines. Vasopressin has also been studied in a chart review and a weak RCT showing some benefit.…”
Section: Statement: Epinephrine Increases Metabolic Abnormalities Commentioning
confidence: 99%
“…Auch beim simulierten Thoraxtrauma mit hämorrhagischem Schock konnte mit Vasopressin der Kreislauf stabilisiert und die Letalität gesenkt werden [11]. Diese Beobach tungen aus Forschungslaboren decken sich mit klinischen Erfahrungen bei der Therapie von unkontrollierten hämorrhagischen Schockzuständen in Deutschland, Indien, Japan und Öster-reich [13,26,28,35].…”
Section: Vasopressin Beim Schweren Hämorrhagischen Schockunclassified
“…eine erfolgreiche Defibrillation im traumatischen Kreislaufstillstand ermöglichte [13,19]. Diese Ergebnisse wurden auch von Untersuchern in Deutschland [27], Japan [35] und Indien [28] …”
Section: Erforderliche Patientenzahl Und Dauer Der Studieunclassified
See 1 more Smart Citation